2002
DOI: 10.1017/s000944390200027x
|View full text |Cite
|
Sign up to set email alerts
|

The Resilience of Guanxi and its New Deployments: A Critique of Some New Guanxi Scholarship

Abstract: In addressing claims that the art of guanxi is declining in China's current incorporation of capitalism, this article argues that guanxi must be treated historically as a repertoire of cultural patterns and resources which are continuously transformed in their adaptation to, as well as shaping of, new social institutions and structures, and by the particular Chinese experience with globalization. The article takes issue with approaches which treat guanxi as a fixed essentialized phenomenon which can only withe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
219
0
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 326 publications
(229 citation statements)
references
References 3 publications
5
219
0
5
Order By: Relevance
“…Like Guthrie, however, we found that participants are actually prepared to express a wide range of views on both guanxi and guanxi practice, indicating that while it is a sensitive topic it can still be investigated in some depth. We would agree with Yang (2002) who argues that, given the sensitive nature of guanxi research, gathering authentic data requires that the researcher spends time in the field building trust with participants in naturalistic settings, which is what was attempted in this study. While not without its problems, we would suggest that, providing there is an element of researcher reflexivity in both the interview process itself, and in the subsequent interpretation of the data, then this kind of data can have a high degree of ecological validity (Creswell and Miller 2000).…”
Section: Limitations and Directions For Further Researchsupporting
confidence: 52%
“…Like Guthrie, however, we found that participants are actually prepared to express a wide range of views on both guanxi and guanxi practice, indicating that while it is a sensitive topic it can still be investigated in some depth. We would agree with Yang (2002) who argues that, given the sensitive nature of guanxi research, gathering authentic data requires that the researcher spends time in the field building trust with participants in naturalistic settings, which is what was attempted in this study. While not without its problems, we would suggest that, providing there is an element of researcher reflexivity in both the interview process itself, and in the subsequent interpretation of the data, then this kind of data can have a high degree of ecological validity (Creswell and Miller 2000).…”
Section: Limitations and Directions For Further Researchsupporting
confidence: 52%
“…24 Since the end of the Soviet Union the relevance of blat in economic life is often believed by many traders to have become restricted to close social bonds and replaced by a stronger impact of monetary aspects beyond that. Yet, the influence of guanxi, as Mayfair Yang argues in her seminal work (Yang 1994(Yang : 2002, continues to shape business 24 Guanxi such as blat refers to interpersonal exchange systems based on social ties that ensure the reciprocal access to certain resources (Ledeneva 1998). interactions and relations since China's opening-up. 25 It is important to note that Yang suggests an increasing role of guanxi in strategies 'to locate and maintain supply sources for new commercial ventures (Yang 2002: 463) In trans-border bazaar trade, guanxi has taken on a translocal form and become an essential element in the 'art of neighbouring' relevant for business.…”
Section: Strengthening Trust Acting Morallymentioning
confidence: 99%
“…Guanxi is an essential Chinese word with multipart thoughts and has been studied by academics in the field of social sciences (Hwang, 1987;Luo, 1997;Tsang, 1998;Wong & Chan, 1999;Yang, 1994Yang, , 2002Lu, 2012). Anthropologist Fei Xiaotong proposed the Chaxu mode in 1948 to clarify the interactive relationships among the Chinese.…”
Section: Guanxi Renqing and Justice Theorymentioning
confidence: 99%